Hermaphroditism, medical science and sexual identity in Spain, 1850-1960 - Cleminson, Richard; Vázquez García, Francisco, 1961- (Iberian and Latin American studies., 2009)
This is the first book in English to analyse the medical category of 'hermaphroditism' in Spain over the period 1850-1960. It attempts to show how the relationship between the male and female body, biological 'sex', gender and sexuality constantly changed in the light of emerging medical, legal and social influences.